Gene‐by‐gene interactions associated with the risk of conotruncal heart defects. Issue 1 (18th December 2019) - Lyu, Chen; Webber, Daniel M.; MacLeod, Stewart L.; Hobbs, Charlotte A.; Li, Ming
Abstract: Background: The development of conotruncal heart defects (CTDs) involves a complex relationship among genetic variants and maternal lifestyle factors. In this article, we focused on the interactions between 13 candidate genes within folate, homocysteine, and transsulfuration pathways for potential association with CTD risk. Methods: Targeted sequencing was used for 328 case‐parental triads enrolled in the National Birth Defects Prevention Study (NBDPS). To evaluate the interaction of two genes, we applied a conditional logistic regression model for all possible SNP pairs within two respective genes by contrasting the affected infants with their pseudo‐controls. The findings were replicated in an independent sample of 86 NBDPS case‐parental triads genotyped by DNA microarrays. The results of two studies were further integrated by a fixed‐effect meta‐analysis. Results: One SNP pair (i.e., rs4764267 and rs6556883) located in gene MGST1 and GLRX, respectively, was found to be associated with CTD risk after multiple testing adjustment using simple M, a modified Bonferroni correction approach (nominal p ‐value of 4.62e‐06; adjusted p ‐value of .04). Another SNP pair (i.e., rs11892646 and rs56219526) located in gene DNMT3A and MTRR, respectively, achieved marginal significance after multiple testing adjustment (adjusted p ‐value of .06). Conclusion: Further studies with larger sample sizes are needed to confirm and elucidate these potential interactions. Abstract : To evaluate the interaction of two genes associated with conotruncal heart defects, we applied a conditional logistic regression model for all possible SNP pairs within two respective genes by contrasting the affected infants with their pseudo‐controls. One SNP pair located in gene MGST1 and GLRX, respectively, was found to be associated with CTD risk after multiple testing adjustment using simpleM, a modified Bonferroni correction approach (nominal p‐value of 4.62e‐06; adjusted p‐value of 0.04). Another SNP pair located in gene MTRR and DNMT3A, respectively, achieved marginal significance after multiple testing adjustment (adjusted p‐value of 0.06).